Opportunities and Implications of the Report on Objectives of Financial Statements - Sorter, George H.; Gans, Martin S. (Journal of Accounting Research, 1974)
George H. Sorter, Martin S. Gans, Opportunities and Implications of the Report on Objectives of Financial Statements, Journal of Accounting Research, Vol. 12, Studies on Financial Accounting Objectives: 1974 (1974), pp. 1-12